The references to Lermontov in Vampilov’s play "Duck Hunt" - Прохорова, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The goal of the present essay is to reveal Lermontov references in Vampilov’s play Duck Hunt. The analysis is carried out on the basis of the key motifs, allusions, reminiscences and structural models referring to A Hero of our Time and Lermontov’s lyrics.